351 Effects of level and source of fat in the diet of gestating beef cows on progeny performance. (7th December 2018) - Añez-Osuna, F; Penner, G; Fitzsimmons, C; Dugan, M; Campbell, J; Jefferson, P; Lardner, H; McKinnon, J
Abstract: A two-year study was conducted to evaluate the effects of level and source of fat in the diet of gestating beef cows on progeny performance. Each year, 75 multiparous pregnant Angus cows (182 ± 4.8 d pre-calving) were randomly assigned to 15 pens, which were randomly assigned to one of three dietary treatments: a low-fat diet (LF; 1.4 ± 0.03% EE) comprised of 72% forage and 28% barley grain, and two high-fat diets (HF; 3.3 ± 0.03% EE) where a canola seed (CAN) or a flaxseed (FLX) based pellet were included to provide 300 g/cow/d of fat as MUFA or PUFA sources, respectively. Diets were formulated to be iso-caloric, iso-nitrogenous, and to meet nutrient requirements for the last two trimesters of gestation. All cows and calves were fed and managed similarly after calving. Data were analyzed as a randomized complete block design with contrasts to separate the effects of level (LF vs. HF) and source (CAN vs. FLX) of fat. Calving dates were not different ( P =0.80) among treatments. Calves from HF cows were heavier ( P ≤0.04) at birth (43.0 ± 0.5 vs. 40.0 ± 0.3 kg) and slaughter (627 ± 7.1 vs. 601 ± 11.4 kg) than those from LF cows. When data were analyzed according to sex, bull-calves from HF cows were heavier ( P <0.01) at birth than those from LF (44.9 ± 0.7 vs. 41.5 ± 0.5 kg) with no difference ( P =0.70) between bull-calves from CAN (44.7 ± 0.7 kg) and FLX (45.1 ± 1.2 kg) cows. At slaughter, steers from HF cows showed greater cumulative-ADG (1.32 ± 0.02 vs. 1.26 ± 0.02 kg/d), shrunk-BW (629 ± 7.5 vs. 598 ± 9.5 kg), and HCW (371 ± 4.3 vs. 352 ± 5.2 kg) than those from LF, with no difference ( P ≥0.11) between steers from CAN and FLX cows. No differences ( P ≥0.10) were found on heifer performance. These results indicate that male progeny performance can be enhanced by manipulating the level of fat in the diet of gestating beef cows, possibly due to developmental programming.